Supreme injustice how the High Court hijacked election 2000 - Dershowitz, Alan M.; Oxford eBooks (New York ; Oxford : Oxford University Press, 2001)
Alan Dershowitz is especially well-qualified to comment upon the disgraceful elections of 2000. He concludes that the Supreme Court's reputation has been sullied and that by setting such an unfavourable precedent the American judicial system will be criticised for its lack of fairness at home and abroad.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Bush, George W. -- 1946- -- Trials, litigation, etc; Gore, Albert, -- 1948- -- Trials, litigation, etc; Contested elections -- United States; Contested elections -- Florida; Presidents -- United States -- Election -- 2000.; Electronic books